2019
DOI: 10.1111/pan.13653
|View full text |Cite
|
Sign up to set email alerts
|

Intra‐operative temperature monitoring with cutaneous zero‐heat‐ flux‐thermometry in comparison with oesophageal temperature: A prospective study in the paediatric population

Abstract: Background: Maintenance of thermal homeostasis is of crucial importance in the anesthetized pediatric patient. Gold-standard methods for central core temperature measurement are however inappropriately invasive and impractical in daily practice.The SpotOn sensor uses zero-heat-flux thermometry technology and claims to bypass the invasiveness of classical methods and still accurately display central core temperatures. Up to date no formal analysis of this method in children has taken place. Aims:The primary obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 23 publications
8
26
1
Order By: Relevance
“…Correctly placed, it lies directly between the left atrium and the descendent aorta and is therefore far away from the potentially cooling airway [20]. Our main finding of a positive bias is in accordance with a previously published study in children by Carvalho et al [16] who found a bias of +0.14 °C with 95% limits of agreement of −0.39 to 0.66 °C. Although our observed bias of +0.26 °C was relatively high, the limits of agreement were tight.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Correctly placed, it lies directly between the left atrium and the descendent aorta and is therefore far away from the potentially cooling airway [20]. Our main finding of a positive bias is in accordance with a previously published study in children by Carvalho et al [16] who found a bias of +0.14 °C with 95% limits of agreement of −0.39 to 0.66 °C. Although our observed bias of +0.26 °C was relatively high, the limits of agreement were tight.…”
Section: Discussionsupporting
confidence: 91%
“…Second, heads of infants and children consist of thinner skull bones resulting in a closer proximity of the skin to the highly perfused brain [28]. Additionally, if the device uses correction algorithms that are based on the anatomical features of an adult, slight overestimation of temperature in young children might be the consequence that Carvalho et al [16] and we have observed.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Ideally, a non-invasive, quick to apply measurement system would be preferable, which could be used in the entire perioperative period [ 17 ]. Presently, several non-invasive thermometers are available, and are gaining more and more interest in children’s medicine [ 17 , 72 , 73 ]. However, to date, neither technique has been evaluated thoroughly in children [ 74 ].…”
Section: Monitoring Of Core Temperaturementioning
confidence: 99%